Contamination‐Assisted Rather Than Metal Catalyst‐Free Bottom‐Up Growth of Silicon Nanowires. Issue 22 (25th October 2021) - Dashtestani, Ashkan Djaberi; Moeinian, Ardeshir; Biskupek, Johannes; Strehle, Steffen
Abstract: Well‐established metal‐catalyzed vapor–liquid–solid (VLS) growth represents still undoubtedly the key technology for bottom‐up synthesis of single‐crystalline silicon nanowires (SiNWs). Although various SiNW applications are demonstrated, electrical and optical properties are exposed to the inherent risk of electronic deep trap state formation by metal impurities. Therefore, metal catalyst‐free growth strategies are intriguing. The oxid‐assisted SiNW synthesis is explored and it is shown that contamination control is absolutely crucial. Slightest metal impurities, such as iron, are sufficient to trigger SiNW growth, calling into question true metal catalyst‐free SiNW synthesis. Therefore, the term contamination‐assisted is rather introduced and it is shown that contamination‐assisted SiNW growth is determined by the chemical surface treatment (e.g., with KOH solution), but also by the crystal orientation of a silicon substrate. SiNWs are grown in this regards in a reproducible manner, but so far with a distinct tapering, using a conventional gas‐phase reactor system at temperatures of about 680 °C and monosilane (SiH4 ) as the precursor gas. The synthesized SiNWs show convincing electrical properties compared to Au‐catalyzed SiNWs. Nevertheless, contamination‐assisted growth of SiNWs appears to be an important step toward bottom‐up synthesis of high‐quality SiNWs with a lower risk of metal poisoning, such as those needed for CMOS and other technologies. Abstract : Metal catalyst‐free synthesis of silicon nanowires is analyzed and discussed considering the role of metal impurities using a gas‐phase reactor system at temperatures of about 680 °C and monosilane as precursor gas. It is shown that minute concentrations of metal impurities, such as iron, are sufficient to trigger SiNW growth, calling into question a truly metal catalyst‐free SiNW synthesis.